Survey the impact of the optimistic and the pessimistic behaviors on occupational and organizational attitude - Amin Reza Kamalian; Mohammad Kouhi Khor (پژوهش‌های مدیریت عمومی, 2016)
The aim of this research is survey the impact the role of optimistic and pessimistic behaviors (organizational pessimism) in predicting and explaining occupational and organizational attitude of employees. The research method in terms of purpose is an applicable research and in terms of data gathering method, is descriptive-correlation. Statistical society of this research includes 130 employees of Organization of Industries and Mine of Zahedan province in the year 1395 and 90 of them were selected through random sampling as the sample of the research. Research data is gathered through three questionnaires of occupational and organizational attitude, optimistic behaviors and organizational pessimism and their validity was approved by using convergent validity and their reliability was approved by using Cronbach’s alpha and composite reliability. Research hypothesis were verified through structural equation modeling with PLS software. Findings show that organizational pessimism has a negative effect on the occupational and organizational attitude of the employees with loading factor of -0.470, and optimistic behaviors have a positive effect on the occupational and organizational attitude of the employees with loading factor of 0.404.